Loss of thrombospondin transcriptional activity in nickel-transformed cells. - Salnikow, K (1994)
mRNA from normal Chinese hamster embryo (CHE) cells was transcribed to cDNA and subtracted with an excess of mRNA from Chinese hamster embryo cells transformed by nickel compounds. Here we report the recovery of a sequence found to be highly homologous to the mouse thrombospondin 1 gene that was obtained by this subtraction procedure. Since thrombospondin is antiangiogenic, cancer cells expressing high levels of thrombospondin cannot grow in vivo because capillaries will not proliferate to cells secreting thrombospondin. To examine expression of thrombospondin, normal CHE cells were stained with monoclonal antibodies to human thrombospondin. The protein was present abundantly in the cytoplasm of normal cells but at greatly reduced levels in Ni-transformed cells. Analysis of mRNA by Northern (RNA) blot revealed transcripts in normal cells but little thrombospondin mRNA in Ni-transformed cells. Loss of thrombospondin mRNA expression was related to Ni treatment rather than transformation, since Ni-resistant cells also exhibited fewer thrombospondin transcripts than did wild-type cells. Digestion of genomic DNA with various combinations of restriction enzymes revealed thrombospondin gene patterns that were identical in both cell types, suggesting that there were no major deletions or rearrangements of the gene in the nickel-transformed cells. The inactivation of the thrombospondin gene was further investigated by analyzing the promoter activity of this gene linked to a chloramphenicol acetyltransferase (CAT) reporter plasmid that was transfected into normal and Ni-transformed cells. The CAT activity in normal cells was significantly higher than in Ni-transformed cells, suggesting that the promoter region of thrombospondin was less efficiently transcribed in Ni-transformed cells. We studied the consequences of enhanced expression of the retinoblastoma (Rb) gene, a known tumor suppressor gene, on CAT transcription driven by the human thrombospondin promoter. Cotransfection of an expression vector containing the mouse Rb gene greatly enhanced the transcription from the thrombospondin promoter such that the expression was higher in normal cells than in transformed cells.